Persepsi Suharto dan Perubahan Kebijakan Luar Negeri Indonesia terhadap Cina pada Awal Orde Baru - Hafid Adim Pradana (Universitas Diponegoro, 2016)
Leadership change from Sukarno to Suharto had given impact to Indonesia foreignpolicies. One of many changes of Indonesia foreign policies in Suharto regime is the severance ofdiplomatic relations with China. This paper aim to explain the Indonesia’s foreign policy change inthat time, especially the severance of diplomatic relations with China in 1967. Despite it becomes ahistorical relic, a case study of Indonesia’s foreign policy under Suharto remains important sincethere have been no specific research focusing on the severance of diplomatic relations betweenIndonesia and China. Using Perception Theory from Ole R. Holsti as the tool of analysis, thispaper concludes that the deteriorating relations between Indonesia and China in 1967 wasinfluenced by Suharto’s perception considered that China is a threat to Indonesia following theattempted coup in 1965.Keywords: Suharto’s perception, Indonesia’s foreign policy, China